Letter (copy) : Grant - Citrine, Walter, 1887-1983
037-0009-001 HVT/FC/92. Secretary's. 14th December, 1937. Mr. Wilfrid Roberts, M.P. The National Committee for the Care of Basque Children, 53 Marsham Street, Westminster, S.W.1. Dear Mr. Roberts, GRANT. I have pleasure in enclosing a further cheque for £500 resulting from the special appeal of the National Council of Labour for Basque children. It is desired that £250 of this amount should be devoted to the ordinary purposes of the Committee in maintaining the children in this country, and that the remaining £250 should be regarded as a contribution to the Basque Children's Committee specially earmarked to assist them with the expenses involved in the repatriation of the children. Yours sincerely, General Secretary, Cheque - £500. 292/946/37/9